Biometric changes in highly myopic eyes before and after phacoemulsification with intraocular lense implantation - N. G. Zavgorodnia; N. V. Mykhailenko (Kazimierz Wielki University, 2021)
High short-sightedness is a complicating factor in phacoemulsification cataract affecting the achievement of high visual results. There are no data in the literature that would reflect changes in the biometric parameters of eyes with high myopia after cataract phacoemulsification with intraocular lens implantation. The authors have shown the reliability of this surgical treatment, the absence of complications and a negative effect on the hydrodynamics of the eye. Patients underwent the ophthalmic examination and for patients preparing for phacoemulsification + IOL: A- and B-scanning, endothelial microscopy, optical biometry. In the group of patients with high myopia, regardless of the age, ranged from 3.1 mmto 3.9 mmwith a mean of 3.52 ± 0.34 mm(variation within 10%), while in the group of patients with myopia and concomitant cataract the fluctuations in anterior chamber depth were recorded in the range from 2.6 mmto 4.4 ± 0.1 mmwith average values of 3.14 ± 0.038 mm(variation within 25%). In the dynamics of treatment, a significant reduction in intraocular pressure according to Maklakov by 6.9% was noted in 6 months from baseline (p <0.001) - from 18.6 ± 2.34 to 17.4 ± 1.09 mmHg. Art. At the same time, it should be emphasized that the main effect of reducing intraocular pressure was expected already within 1 month (17.9 ± 1.06 mmHg) after surgery (3.9%, p = 0.006), followed by decrease by 3.1% after 6 months of follow-up (p = 0.008). The research results showed a direct correlation between the endothelial layer density and the anterior chamber depth. Thus, before surgery r = 0.248, and after surgery r = 0.119, i.e. after phacoemulsification with IOL implantation, the density of the endothelial layer depends on changes in the anterior chamber depth (p <0.05). This research has shown that phacoemulsification with IOL implantation is accompanied by positive changes in the size of the mutually located structures of the anterior chamber of the eyeball.